Two intercultural performances: Double Nora and Resurrection Day - Mori, Mitsuya (Nordlit, 2015)
I have so far directed two plays of Ibsen as the intercultural performance, that is, the collaboration of the modern theatre with noh, a traditional Japanese theatre, which was established as an artistic theatre form in the 14th century. The first production was Double Nora, based on A Doll’s House, which premiered at a noh theatre in Tokyo in 2005, and the second was Resurrection Day, based on When We Dead Awaken, performed at the Ibsen Festival in Tokyo in 2010. In both productions, professional noh and modern theatre actors appeared together in their own acting styles. At the Ibsen Conference in Tromsø in June 2012, brief scenes of the two productions were shown. But here in the present article the performances are partly described, and the interactive relationship between different acting styles of noh and modern theatre is examined. A new and difficult experiment of Resurrection Day was to try a conversation between the main noh actor and the modern actress. The experiment was possible because the performance took place not on a noh stage in a unique form but on an ordinary stage in a modern theatre. Thus, some problems involved in the intercultural performance of Ibsen are investigated.